Gestión Pedagógica en el aula: Clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica de los centros educativos urbana Luz de América y rural“Ing. Alfonzo Valdivieso, de la ciudad de Cariamanga cantón Calvas provincia de Loja, 2012-2013 - Montero Torres, Bolivar Alejandro (2013)
The researched topic covers the Educational Management in the Classroom: School social climate from the perceptions of students and teachers of the seventh year of basic education in schools: Urbana school " Light of America " and the Rural School, " Mr. Alfonzo Valdivieso " .2012-2013 Immediately over the research process , the objectives designed and proposed by the university were met , the employment surveys of school climate CES Moos and Trickett , with Ecuadorian adaptation for teachers and students , and questionnaire management of teacher learning taken from the Ministry of Education Ecuador (2011 ) and the observation sheet to teacher learning management also taken the ministry. From the results we can systematize the teaching classroom management and social climate, depend on each other and are within acceptable parameters within the educational process at both institutions. Except for the limited use of ICT , for fear of technology and lack of training for teachers . Proposed intervention as a training in the use of multimedia tools aimed at teachers was raised to improve teaching skills.